Papel da matematização nas explicações de professores e alunos em disciplinas de física na formação inicial de professores - Vizcaino Arevalo, Diego Fabian [UNESP] (2013)
The main objective of this research is to established parameters for using of Matematization of Physics as an effective component in the construction of explanations, in order to contribute to the improvement of teaching and learning of physics on initial education of teachers. Thus, we formulated the research problem: What possible relations operate in the use of Mathematization of Physics in the construction of explanations in educational activities for Teaching Physics, held in an undergraduate course of teachers Physics?. This problem was split into three investigative questions that inquired about meanings attributed to Mathematization of Physics in: teaching activities of teachers, textbooks used in these activities, and explanations of undergraduate students. For this purpose, we study a theoretical framework that allowed us to investigate in search results over the last decades for the teaching of physics specifically related studies on the use of mathematics. Based on this study, we obtained three categories on the Mathematization of Physics in the process of teaching improvement. They are: (1) Mathematization from mathematical modeling, (2) Mathematization from physical-mathematical process, (3) Mathematization to complment the phenomenological study. Thus, we use these three as analysis categories of the data. The nature of this research was qualitative and we used methodologies such as, non-participant observation, questionnaires and textual analysis of textbooks teaching, on an undergraduate course from a public university in the state of São Paulo, Brazil. Briefly we can conclude that the perspectives of teachers coincide in some aspects of Mathematization through mathematical modeling, and in the second, they coincide with Mathematization as a complement of phenomenological study, bur turn away them in relation to the type of problems that are solved in the teaching process, since in general, all agree to work...